THE IMPORTANCE OF CHARACTER EDUCATION IN ELEMENTARY SCHOOL CHILDREN IN A DIGITAL AGE - Aminan; Akmaluddin; Siti Mayang Sari; Muhammad Kaulan Karima (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Character education is an attempt to apply religious, moral, ethical values to students through science, assisted by parents, teachers, and society which is very important in the formation and development of students' character. Every child has good potential from birth, but this potential must continue to be honed and socialized properly so that the character of each child is formed and develops optimally. In this all-digital era, children can easily use digital media. The digital age, which not only has positive impacts, but also negative impacts, is a task for educators, parents and adult society in guiding and monitoring what children do with their digital media, so that children are able to make the best use of their digital media and get the maximum benefits. both for himself and his life.